Sustainability Disclosure of GRI: Is Management Impression? - Putri, Yayang Novealita Wahono; Ekasari, Kurnia; Wahyuni, Hesti (Journal of Applied Business, Taxation and Economics Research, 2024)
This research aims to comparing investigations sustainability reporting disclosure, between the top five F&B company in Indonesia and associate it with the management impression theory. The role of SR auditor is also in the spotlight issue. This research uses descriptive qualitative statistic method to analyze GRI disclosure the top five F&B company in Indonesia using their SR data from 2020-2021. The larger size of company in direct propotion to the number of GRI points disclosed. The greater number of GRI points disclosed always indicates that in preparing their SR, the company is assisted by an independent as assurance. Thus, management impression can be reduced even if it appears a little. Proves that the most important issue faced by the company is the most material to report and shows that indirectly sustainability report is a tool to improve the company’s image. Future research directions have provided coverage wider area of the company and link it to auditing standards furthermore (specific aspect) for reliable sustainability reports that can be useful for stakeholders.